The OISIN framework : ontology interoperability in support of semantic interoperability - O'Sullivan, Declan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2006)
The promise of ontologies is in the sharing of an understanding of a domain that can be communicated between people and application systems (Fensel 2003). However, different ontologies arise due to the natural human diversity involved in modelling a domain. In other words, ontologies are normally created from a particular perspective. If the applications of an individual or company that use an ontology, need to interact with applications of other individuals or organisations that use different ontologies, there will be a need to map between the multiple ontologies either at inter-personal, intra-organisational or inter-organisational levels (Hameed et al. 2004). It is envisaged that such ontology mapping will be beneficial in a wide range of scenarios that require support for semantic interoperability, including: web service composition, distributed information querying, e-commerce catalogue matching, and personalisation of information. However, in order for the use of such mappings to gain widespread acceptance, a practical ontology mapping lifecycle needs to be put in place. In addition, given the potential importance of such ontology mappings to organisations, there is a need for such mappings to be created as part of some engineered process rather than as a result of ad hoc activities. This thesis identifies the activities, information artefacts, heuristics and guidance required to support a practical ontology mapping process, and examines how they can be coordinated and sequenced in the ontology mapping process. The thesis proposes the OISIN framework comprising an ontology mapping process supported by software tools. The framework: supports a full ontology mapping lifecycle; is extensible and adaptable; and supports the creation of “relevant mappings”, ranging from supporting a user’s determination of mappings to an application’s determination of mappings. The thesis details the specification of the ontology mapping process, describes the design and implementation of the supporting software tools, and presents the evaluation of the process and tools.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin